Automatic system for thermal damage detection in manufacturing process with Internet monitoring - Dotto, Fábio R. L. [UNESP]; De Aguiar, Paulo R. [UNESP]; Bianchi, Eduardo C. [UNESP]; Serni, Paulo J. A. [UNESP]; Thomazella, Rogério [UNESP] (Springer Nature, 2006)
This work involved the development of a smart system dedicated to surface burning detection in the grinding process through constant monitoring of the process by acoustic emission and electrical power signals. A program in Visual Basic® for Windows® was developed, which collects the signals through an analog-digital converter and further processes them using burning detection algorithms already known. Three other parameters are proposed here and a comparative study carried out. When burning occurs, the newly developed software program sends a control signal warning the operator or interrupting the process, and delivers process information via the Internet. Parallel to this, the user can also interfere in the process via Internet, changing parameters and/or monitoring the grinding process. The findings of a comparative study of the various parameters are also discussed here. Copyright © 2006 by ABCM.
Keywords: Acoustic emission; Burn detection; Electrical power; Grinding; Internet; Monitoring; Internet monitoring; Acoustic emissions; Analog to digital conversion; Computer software; Electric power transmission; Thermoanalysis; Online systems